Extinction: Stories of unravelling and reworlding - Chrulew, Matthew; De Vos, Rick (2019)
Extinction challenges our thinking and writing. Such overwhelming disappearance of ways of being, experiencing and making meaning in the world disrupts familiar categories and demands new modes of response. It requires that we trace multiple forms of both countable and intangible loss, the unravelling of social and ecological communities as a result of colonialism and capture, development and defaunation and other destructive processes. It brings forth new modes of commemoration and mourning, and new practices of archiving and survival. It calls for action in the absence of hope, and for the recognition and nourishment of new generativities: new modes of assemblage and attachment, resurgence and reworlding, commoning, composting and caring for country.